2019
DOI: 10.2478/amma-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Congestive Heart Failure and Upper Digestive Endoscopic Lesions

Abstract: Objective: To evaluate the impact of congestive heart failure and the most important clinical and pathological factors on severe upper digestive mucosal lesions.Methods: The study included 749 patients referred for upper digestive endoscopy, divided into two groups: 140 subjects with congestive heart failure (study group) and 609 subjects without heart failure (control group).Results: Severe endoscopic lesions quantified according to Lanza score (OR = 3.84, 95% IC: 2.62-5.62), active/inactive gastritis (OR = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Antiplatelets (e.g., aspirin [ 159 ] and clopidogrel [ 160 ]) and/or anticoagulants (e.g., warfarin [ 161 ]) are known to increase GI bleeding by causing GI lesions, especially if used in combination [ 162 , 163 , 164 ]. Such complex dual and triple antithrombotic drug combinations increase the risk of GI bleeding substantially [ 165 , 166 ]. Remarkably, the presence of comorbidities amplifies the risk of GI bleeding when these agents are used, with HF being an independent risk factor [ 162 , 167 , 168 , 169 ].…”
Section: Causes Of Iron Deficiency In Heart Failurementioning
confidence: 99%
“…Antiplatelets (e.g., aspirin [ 159 ] and clopidogrel [ 160 ]) and/or anticoagulants (e.g., warfarin [ 161 ]) are known to increase GI bleeding by causing GI lesions, especially if used in combination [ 162 , 163 , 164 ]. Such complex dual and triple antithrombotic drug combinations increase the risk of GI bleeding substantially [ 165 , 166 ]. Remarkably, the presence of comorbidities amplifies the risk of GI bleeding when these agents are used, with HF being an independent risk factor [ 162 , 167 , 168 , 169 ].…”
Section: Causes Of Iron Deficiency In Heart Failurementioning
confidence: 99%
“…This study showed a decrease in endoscopic procedures being performed throughout the follow-up period in patients with heart failure. These findings may be due to a decrease in the incidence of upper GI bleeding as a cause of anemia in recent years, greater use of gastric protectors such as omeprazole, and a decrease in the use of non-steroidal anti-inflammatory drugs or anti-aggregants at high doses [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an elevated level of heart rate is also noticed in these individuals. 14,15 The etiology of the pylori bacterium influences heart diseases also; antibodies of the such bacterium are found in patients with cardiovascular diseases. Moreover, it makes digestive complications and disrupts the mechanism of various factors including cytokines, fibrinogen, triglycerides, lipoprotein, C-reactive protein, and white blood cells.…”
Section: Introductionmentioning
confidence: 99%
“…It also triggers other problems that lead to cardiovascular diseases such as atherosclerosis and the prothrombic state of heart diseases. 4,14,16,17 Digestive manifestations are either directly or indirectly influenced by helicobacter pylori infection such as IL-1, TNF-a, interferon (IFN)-g, leukotriene C4, and platelet-activating factor. It also contributes to inflammatory and chronic immune responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation